2020
DOI: 10.1007/s00464-020-08182-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reflux following sleeve gastrectomy and one anastomosis gastric bypass: 1-year results from a randomized open-label controlled trial

Abstract: Background Recent reports have demonstrated that de novo reflux and worsening of pre-existing symptoms occur after SG; concerns are still expressed about the risk of symptomatic biliary reflux gastritis and oesophagitis. The aim of our study was to investigate and compare the rate of postoperative acid and non-acid reflux following Mini-/One anastomosis gastric bypass (MGB/OAGB) and laparoscopic sleeve gastrectomy (LSG). Study design A prospective randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 67 publications
(76 reference statements)
1
11
0
1
Order By: Relevance
“…This has been investigated by Tolone et al They have demonstrated, using high-resolution impedance manometry, the pressure gradient between the sleeve-shaped stomach and the jejunum acts as an active pump facilitating the flow of the bile into the intestine, while the length of the pouch avoids reflux into the oesophagus [20]. Specifically, another randomized clinical trial has also demonstrated that AET% (acid-exposure time) and rate of esophagitis are significantly higher after LSG when compared to MGB/OAGB; therefore, this procedure should be preferred in case of preoperative subclinical reflux or low grade (A) esophagitis [21].…”
Section: Discussionmentioning
confidence: 99%
“…This has been investigated by Tolone et al They have demonstrated, using high-resolution impedance manometry, the pressure gradient between the sleeve-shaped stomach and the jejunum acts as an active pump facilitating the flow of the bile into the intestine, while the length of the pouch avoids reflux into the oesophagus [20]. Specifically, another randomized clinical trial has also demonstrated that AET% (acid-exposure time) and rate of esophagitis are significantly higher after LSG when compared to MGB/OAGB; therefore, this procedure should be preferred in case of preoperative subclinical reflux or low grade (A) esophagitis [21].…”
Section: Discussionmentioning
confidence: 99%
“…The OAGB with a tailored limb length of about 200 cm has shown to achieve good weight loss for patients with BMIs over 50 kg/m 2 [38] and has shown superiority when compared to the SG [39][40][41]42]. A systematic review by Parmar et al reported mean %EWL of 90.75%, three years after OAGB patients with BMIs over 50 kg/m 2 [43].…”
Section: Discussionmentioning
confidence: 99%
“…Roux-en-Y gastric bypass is lauded for ameliorating GERD post-operatively [ 20 ], mechanistically attributable to hastened gastric emptying through an unrestricted gastrojejunostomy [ 21 ]. Similarly, OAGB reduces GERD post-operatively, with reduced acid exposure time, and lower number of acidic reflux events on impedance pH demonstrated 12 months post-operatively [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a recent randomised controlled trial demonstrating complete endoscopic regression of pre-operative Los Angeles grade A or B esophagitis in 90% of patients at 12-month post-OAGB [ 23 ]. The long, narrow gastric pouch and widely patent gastrojejunostomy proposed as likely mechanistic explanations [ 22 ]. Studies by Lasheen and Shenouda reported post-operative gastroesophagitis in 32.5% of patients at 9 months and 55% at 6 months, respectively; however, no comment was made about whether these findings were de novo post-operative findings or had been present pre-operatively [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%